Financing higher education: the case for a graduate tax - Dietsch, Peter (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2006)
The debate whether university education should be “free” seems misconstrued. Even in a system without tuition fees, someone will have to foot the bill. This paper argues that from the viewpoint of justice, a strong case can be made in higher education for adopting the beneficiary pays principle, and for institutionalising it in the form of a graduate tax. My evaluation from the perspective of justice will focus on the comparison between a “free” university system funded through the general tax system on the one hand, and one financed through a graduate tax on the other. On the beneficiary pays principle defended here, the regressive nature of the general-tax-funded higher education system renders it unjust. Furthermore, I believe we have three reasons to favour a graduate tax in practice. First, I will suggest that it does a better job at implementing the beneficiary pays principle. Second, I will argue that even though the distributive outcome of a corrected general-tax-funded education may be just, it is unlikely to be perceived to be just. A third point of comparison between the two approaches to fund higher education will be international mobility, which will reinforce the case for a graduate tax from the viewpoint of justice.